A comparative study on tumour response and treatment toxicities of two cycles versus three cycles of induction chemotherapy followed by concurrent chemoradiotherapy in the management of locoregional advanced head and neck cancer - Swer, Dorafiona; Singh, Laishram Jaichand; Devi, Yumkhaibam Sobita; Panmei, Ruby; Kilari, Lakshmi Tirumala Gowtham; B., Mohan Babu (International Journal of Research in Medical Sciences, 2025)
Background: Locally advanced head and neck squamous cell carcinoma (LA-HNSCC) is being treated by multimodality approached, the rationale of using induction chemotherapy (ICT) is to shrink the tumors, enhance local control, and improved response, supporting the use of multiple ICT cycles. This study, compares two different courses of ICT followed by concurrent chemoradiotherapy to see the improvement in tumour response and treatment toxicities. Methods: A randomized controlled trial conducted at the department of radiation oncology, RIMS, Imphal, from July 2022 to June 2024 after approval was obtained from institutional research ethics board (REB) with a total of 61 patients, where 31 patients recruited in arm-A and 30 patients in arm-B which compares two cycles versus three cycles of ICT followed by chemo-radiotherapy. Tumor response and toxicities were assessed using RTOG and RECIST criteria. Results: Toxicities like oral mucositis, anemia, neutropenia, thrombocytopenia were seen more in arm B as compared to arm A and KFT toxicities were higher in arm A. Late toxicities like dermatitis, xerostomia, subcutaneous fibrosis were observed higher in arm-B. Partial response (PR) was observed better in arm B but progressive disease (PD) and stable disease (SD) were higher in arm A. Conclusions: Arm B showed slightly better tumor shrinkage but had more side effects with mucositis, nausea, and blood-related issues. Late toxicities were slightly higher in arm B. However, these differences were not statistically significant. Overall, both arms showed similar effectiveness. More research is needed to find the ideal number of ICT cycles that maximize response and minimize side effects.